Technological Factors Affecting Biogenic Amine Content in Foods: A Review - Gardini, Fausto; Özogul, Yesim; Suzzi, Giovanna; Tabanelli, Giulia; Özogul, Fatih (Frontiers in Microbiology, 2016)
Biogenic amines (BAs) are molecules which can be present in foods and, due to their toxicity, can cause adverse effects on the consumers. BAs are generally produced by microbial decarboxylation of amino acids in food products. The most significant BAs occurring in foods are histamine, tyramine, putrescine, cadaverine, tryptamine, 2-phenylethylamine, spermine, spermidine and agmatine. The importance of preventing the excessive accumulation of BAs in food is related to their impact on human health and food quality. Quality criteria in connection with the presence of BAs in food and food products are necessary from a toxicological point of view. This is particularly important in fermented foods in which the massive microbial proliferation required for obtaining specific products is often relater with BA accumulation. In this review, up-to-date information and recent discoveries about technological factors affecting biogenic amine content in foods are reviewed. Specifically, BA forming-microorganism and decarboxylation activity, genetic and metabolic organization of decarboxylases, risk associated to BAs (histamine, tyramine toxicity and other BAs), environmental factors influencing BA formation (temperature, salt concentration, pH). In addition, the technological factors for controlling BA production (use of starter culture, technological additives, effects of packaging, other non-thermal treatments, metabolising BA by microorganisms, effects of pressure treatments on BA formation and antimicrobial substances) are addressed.